2019
DOI: 10.1021/acs.energyfuels.9b02728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Retarding Components on Heavy Oil Catalytic Cracking and Their Corresponding Countermeasures

Abstract: Heavy oil could be classified into two parts: one is the easy cracking part, which is the main source of liquid hydrocarbon transportation fuels and industrial chemicals, and the other is the refractory cracking part, which is failed to be cracked by the present technologies and has negative effects on upgrading. Therefore, the efficient method to obtain a higher conversion of heavy oil is needed for the heavy oil processing industry. Coker gas oil (CGO), used as an example of heavy oil, is supposed to be hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…As a whole, the EBVRHC heavy oil characterizing variables which affect conversion according to Eq. 3 are in line with the findings reported in other studies 21, 46 showing that the nitrogen components and condensed aromatics are the retarding components in heavy oil catalytic cracking. The single EBVRHC heavy oil characterizing parameter, which best correlated with the conversion at a CTO of 7.5 (w/w), was the Kw factor.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As a whole, the EBVRHC heavy oil characterizing variables which affect conversion according to Eq. 3 are in line with the findings reported in other studies 21, 46 showing that the nitrogen components and condensed aromatics are the retarding components in heavy oil catalytic cracking. The single EBVRHC heavy oil characterizing parameter, which best correlated with the conversion at a CTO of 7.5 (w/w), was the Kw factor.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, the slope of the FCC conversion decrease during processing of feed blends, which contain secondary gas oils, can be different [1]. Therefore, the processing of vacuum residual oils having different quality in the cokers and in the ebullated-bed vacuum residue hydrocrackers can yield VGOs having different quality that in turn can affect the FCCU performance, where these secondary gas oils are converted [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mass of condensed aromatic hydrocarbons can hardly be cracked into a gasoline fraction for their good chemical stability. Oppositely, those aromatics are more likely to have a condensation reaction, resulting in a high yield of heavy oil and coke product under the catalytic cracking circumstance . Therefore, more macromolecules consisting of the heavy fraction were converted into heavy oil and coke as reflected in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Since its introduction in 1942, fluid catalytic cracking (FCC) has become the main driver for oil refining performance improvement. , Over the years, it was found that FCC is a versatile process that can convert feeds of different originsvacuum oils, residual oils, crude oil, scrap tires pyrolysis oil, polyethylene plastic waste, biomass derived oilsinto high value transportation fuels and light olefin feeds for the petrochemical industry. Among all independent variables which affect the FCC unit (FCCU) performance, the feedstock quality has the biggest impact. While the processing of straight run vacuum gas oils (SRVGOs) in the FCCU is much more straightforward, the processing of secondary gas oils (from coker, visbreaker, and residue hydrocracker) is more challenging . Secondary gas oils are indeed characterized by a higher basic nitrogen content and by a higher level of refractory condensed aromatic compounds. The performance of the FCCU is therefore strictly correlated to the amount and the quality of the secondary gas oil fraction present in the FCC feed blend. , …”
Section: Introductionmentioning
confidence: 99%